Electrochemical oxidation of p-nitrophenol on boron-doped diamond film electrode - JIANG Jing; CUI Zhaolun; ZHANG Chuyan; HUANG Nan (Gongye shui chuli)
p-nitrophenol wastewater is characterized by high chemical oxygen demand(COD), biological hazard and refractory degradation, which is difficult to be treated efficiently using traditional methods. In this paper, the boron-doped diamond (BDD) thin film electrode was employed for the degradation of p-nitrophenol. The effects of current density, flow rate and initial concentration of p-nitrophenol on the degradation of p-nitrophenol were investigated. It indicated that the degradation efficiency increased with higher current density and higher flow rate, but decreased with the increase of initial concentration. Methanol and tert-butanol were used as quenchers to verify the activity of hydroxyl radicals and sulfate radicals. After adding quenchers, the removal rate of p-nitrophenol dropped from 99.5% to 76.2% and 56.2%. Liquid chromatography-mass spectrometry (LC-MS) was conducted to detect the intermediate products of the degradation process with different initial concentrations of p-nitrophenol. The identified degradation pathways consisted of the substitution of hydroxyl radicals for nitro and addition to the benzene ring until the ring splitting. The economics of electrochemical oxidation on BDD electrode were analyzed by calculating current efficiency and energy consumption from detecting COD value, and the ways for future research were proposed.